Micro/nano replication and 3D assembling techniques for scaffold fabrication - Lima, M. J. (2014)
The development of tissue engineering field entails the creation of micro/nanoscale features for cellular alignment and biocompatibility improvement. As replication techniques, hot embossing and soft lithography can be used to produce micro/nanoscale features on biodegradable membranes. Subsequently the generation of 3D scaffolds can be done by means of assembling techniques. Using the described techniques, high resolution of features, as small as 5nm, can be achieved. Nevertheless membrane assembling must be fully studied to avoid feature fluctuations and even collapse of the scaffold. The present review focuses on the state-of-the-art in the replication techniques used to create micro/nanoscale features on biodegradable polymers and assembling approaches to construct scaffolds with the aim of exploring existing advances and limitations of the reported methods.